Ergonomic Evaluation of Work Conditions in Qazvin Dentists and its Association with Musculoskeletal Disorders Using REBA Method - Sakineh Varmazyar; Morteza Amini; Mehdi Kiafar (Islamic Dental Association of Iran, 2012)
Background and Aim: Dynamic and static activities in dentistry, cause musculoskeletal disorders but dentists do not have enough awareness about effects of ergonomic factors on their health. T he aims of this study were to assess ergonomic conditions in dental workstation in Faculty of Dentistry, Qazvin University of Medical Sciences, using REBA method, to investigate the relationship between REBA scores and musculoskeletal disorders and finally, to present corrective solutions .   Materials and Methods: In this cross-sectional study posture assessment of 63 participants were implemented by the REBA method. In order to investigate incidence of musculoskeletal disorders, the standard Nordic questionnaire was used. Data were processed using regression and chi-square tests and the significance level was determinate at P< 0.05 .   Results: The results indicated that 30.2% of participants obtained from11 to 15 scores (very high risk level). Results of the Nordic questionnaire indicated that the highest musculoskeletal disorder report was related to neck region with 50.8 %.   Conclusion: The results showed that 30.2% from the final REBA scores had very high risk level and 51.7% high risk level means that essential corrective and urgent corrective measures are required respectively .